2012
DOI: 10.1590/s0001-37652012005000023
|View full text |Cite
|
Sign up to set email alerts
|

Does Evolution matter?: a case study in Brazil of the effects of an evolutionary-thinking academic atmosphere in postgraduate students' belief in God/religious belief

Abstract: Although the theory of evolution is more than 150 years old, a substantial proportion of the world population does not mention it when explaining the origin of human beings. The usual alternative conception is offered by creationism, one of the main obstacles to full acceptance of evolution in many countries. National polls have demonstrated that schooling and religiosity are negatively correlated, with scientists being one of the least religious professionals. Herein we analyzed both (1) the profile of 1st se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…For example, evolution, stem-cell research, and cloning have been targeted, albeit in varying degrees and from different directions, by religious activists. Also, there is evidence that evolutionary thinking itself may shift scientists away from God-belief (Dias et al 2012;Leigh 2013). On the other hand, not since the time of Galileo have the physical sciences been threatened by religious dogma.…”
Section: Discussionmentioning
confidence: 99%
“…For example, evolution, stem-cell research, and cloning have been targeted, albeit in varying degrees and from different directions, by religious activists. Also, there is evidence that evolutionary thinking itself may shift scientists away from God-belief (Dias et al 2012;Leigh 2013). On the other hand, not since the time of Galileo have the physical sciences been threatened by religious dogma.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the national scenario is different from that of the USP firstperiod biology school. In fact, we found more Cr than Dias et al (2012) did in the veterinary school, a course without contact with the theory of evolution. Why are the national parameters of biology students so dissimilar from those from USP (in biology and veterinary)?…”
Section: Resultsmentioning
confidence: 53%
“…Paradoxically, this indicates that NaE is not the predominant explanation in students' views. Nevertheless, Dias et al (2012) interviewed students from the first graduation period from USP (University of São Paulo, Brazil), the largest university in South America, and found that the proportions of NaE, DGE, and Cr were 79.2, 19.8, and 1%, respectively. The authors compared these findings with those from the veterinary school of the same institution (49.1, 45.6, and 5.3%) and suggested that biology students are more prone to NaE even in early periods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This comes particularly from the fact that religious groups have tried in different occasions to misrepresent the premises of the evolutionary theory, which was first published by the English naturalist Charles Darwin (e.g., Miller et al 2006, Dias et al 2012. Extremists even advocate that this discipline should not be taught in schools.…”
mentioning
confidence: 99%